Description of a new coastal Adota Casey (Coleoptera: Staphylinidae: Aleocharinae) species from Kamchatka - Yoo, In-Seong; Jung, Jong-Keun; Ahn, Kee-Jeong (Zootaxa, 2024)
Adota kamchatkaensis Yoo & Ahn, sp. nov. is described on the coast of Kamchatka, Russia. It is similar to A. ushio (Sawada) and A. madida (Bernhauer) but can be distinguished by the emarginate posterior margin of male abdominal tergite VIII and the different form and structure of the aedeagus and spermatheca. A comparison table of morphological characters, description, habitus photograph, and illustrations of diagnostic characters of this new species are provided.